2018
DOI: 10.3390/molecules23040903
|View full text |Cite
|
Sign up to set email alerts
|

Iron Is the Active Site in Nickel/Iron Water Oxidation Electrocatalysts

Abstract: Efficient catalysis of the oxygen-evolution half-reaction (OER) is a pivotal requirement for the development of practical solar-driven water splitting devices. Heterogeneous OER electrocatalysts containing first-row transition metal oxides and hydroxides have attracted considerable recent interest, owing in part to the high abundance and low cost of starting materials. Among the best performing OER electrocatalysts are mixed Fe/Ni layered double hydroxides (LDH). A review of the available experimental data lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 42 publications
5
71
0
Order By: Relevance
“…[10] Hunter et al reported evidence of Fe 6+ under anodic bias in non-aqueous electrolytes. [14] Co(Fe)O x H y is structurally and electrochemically similar to Ni(Fe)O x H y . [12,13] These,a nd other, results have been used to argue that Fe is the active site in Ni(Fe)O x H y for the OER.…”
mentioning
confidence: 97%
“…[10] Hunter et al reported evidence of Fe 6+ under anodic bias in non-aqueous electrolytes. [14] Co(Fe)O x H y is structurally and electrochemically similar to Ni(Fe)O x H y . [12,13] These,a nd other, results have been used to argue that Fe is the active site in Ni(Fe)O x H y for the OER.…”
mentioning
confidence: 97%
“…DFT calculations have also pointed to the presence of higher Fe oxidation states (>3+) in Ni(Fe)O x H y during the OER that facilitate catalysis . These, and other, results have been used to argue that Fe is the active site in Ni(Fe)O x H y for the OER …”
Section: Figurementioning
confidence: 95%
“…Many sources have reported on Fe 3+ and some claim evidence for Fe 4+ by XAS and Mössbauer spectroscopy, but only for the mixed NiFe oxyhydroxide and clearly not in the Fe‐only catalyst. Also Hunter et al . concluded that Fe in higher oxidation states is the active site in NiFe layered double hydroxide OER catalysts.…”
Section: Introductionmentioning
confidence: 99%